The painful total ankle arthroplasty: a diagnostic and treatment algorithm. Issue 1 (January 2017) - Vulcano, E.; Myerson, M. S.
Abstract : The last decade has seen a considerable increase in the use of in total ankle arthroplasty (TAA) to treat patients with end-stage arthritis of the ankle. However, the longevity of the implants is still far from that of total knee and hip arthroplasties. The aim of this review is to outline a diagnostic and treatment algorithm for the painful TAA to be used when considering revision surgery. Cite this article: Bone Joint J 2017;99-B:5–11.